Effect of auxin on the histology and metabolism of leaf cuttings of Brassica oleracea var. Botrytis - Galle, E. E. C.(Ernst Erich Christian) (Stellenbosch : Stellenbosch University, 2012)
Script (M. Sc. Agric.) -- University of Stellenbosch, 1965.